Bedside Ultrasound in Resuscitation and the Rapid Ultrasound in Shock Protocol. (24th October 2012) - Seif, Dina; Perera, Phillips; Mailhot, Thomas; Riley, David; Mandavia, Diku
Abstract : Assessment of hemodynamic status in a shock state remains a challenging issue in Emergency Medicine and Critical Care. As the use of invasive hemodynamic monitoring declines, bedside-focused ultrasound has become a valuable tool in the evaluation and management of patients in shock. No longer a means to simply evaluate organ anatomy, ultrasound has expanded to become a rapid and noninvasive method for the assessment of patient physiology. Clinicians caring for critical patients should strongly consider integrating ultrasound into their resuscitation pathways.